2017
DOI: 10.1371/journal.pone.0184213
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A affects HepG2 human hepatocellular carcinoma cells glucose metabolism via HIF-1α-dependent and -independent mechanism

Abstract: Orexins are hypothalamic neuropeptides that regulate feeding, reward, wakefulness and energy homeostasis. The present study sought to characterize the involvement of orexin A in glucose metabolism in HepG2 human hepatocellular carcinoma cells, and investigated the role of hypoxia-inducible factor-1α (HIF-1α) in the response. HepG2 cells were exposed to different concentrations of orexin A (10−9 to 10−7 M) in vitro, without or with the orexin receptor 1 (OX1R) inhibitor (SB334867), HIF-1α inhibitor (YC-1) or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…To determine the biological functions of orexin-A in pancreatic cancer, we activated or inactivated the stimulation of OX1Rby incubation with different concentrations (10 −5 , 10 −6 , 10 −7 , and 10 −8 M) of orexin-A with or without treatment of SB408124 (50 nM), an OX1 receptor antagonist to prevent the orexin-A effect on cell proliferation in PANC1 cells (data not shown). We found that treatment with10 −7 M orexin-A can significantly upregulate OX1R expression in PANC1 cells (Figure 3A ), which is consistent with that of previous reports ( 20 , 23 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To determine the biological functions of orexin-A in pancreatic cancer, we activated or inactivated the stimulation of OX1Rby incubation with different concentrations (10 −5 , 10 −6 , 10 −7 , and 10 −8 M) of orexin-A with or without treatment of SB408124 (50 nM), an OX1 receptor antagonist to prevent the orexin-A effect on cell proliferation in PANC1 cells (data not shown). We found that treatment with10 −7 M orexin-A can significantly upregulate OX1R expression in PANC1 cells (Figure 3A ), which is consistent with that of previous reports ( 20 , 23 ).…”
Section: Resultssupporting
confidence: 92%
“…Previous reports have indicated that orexin-A expression might be associated with malignancy in several tumors ( 20 , 23 , 24 ). Therefore, we examined the potential functions of orexin-A in human pancreatic cancer.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Human neuroblastoma cells treated with ORX-A had increased mitochondrial membrane potential [60]. Additionally, in studies using human hepatoma cells [61] and human embryonic kidney cells [62], treatment with ORX-A resulted in increased ATP production that shifted from glycolysis in the cytoplasm to oxidative phosphorylation in the mitochondria. Taken together, these studies indicate that orexin is able to enhance mitochondrial function, biogenesis, and ATP production in mammalian vertebrates.…”
Section: Secretion Of Orexin By Qm7 Cells (A-c) and Effect Of Orexin mentioning
confidence: 99%